The Competitiveness of Global Port-Cities: The Case of Danube Axis (Bratislava, Štúrovo, Komárno), Slovak Republic - van den Bossche, Marten (OECD Publishing, 2013)
This working paper offers an evaluation of the performance of the inland ports of the Slovak Republic within the framework of the Danube Axis, an analysis of the impact of the ports on their territory and an assessment of policies in this field. It examines port performance over the last decades and identifies the principal factors that have contributed to it. The effect of the port on economic and environmental questions is studied and quantified where possible. The major policies governing the ports are assessed, along with policies governing transport and economic development, the environment and spatial planning. Based on the report's findings, recommendations are proposed with a view to improving port performance and increasing the positive effects of the inland ports of Slovak Republic
Keywords: Urban, Rural and Regional Development; Slovak Republic